Managing operational risk among SMEs: the Malaysian perspective - Hamidatun Khusna, Mustafa (2021)
Despite being one of the integral components in fostering Malaysia’s economic growth, small and medium-sized enterprises (SMEs) have failed to attain their full potential due to various challenges. Based on the SMEs Masterplan 2012-2020, the Malaysian government has outlined six key challenges that could impede company performance excellence: innovation and technology adoption, infrastructure, access to financing, legal and regulatory environment, market access and human capital development. These challenges might lead to operational risks, which would likely lower the SMEs performance. The objective of this study is to examine the relationship between operational risk, risk mitigation strategy, and company performance. Specifically, this study focuses on Malaysia’s SMEs manufacturing industry by suggesting agility as part of a mitigation strategy towards enhancing their performance. Although the government has spent billions of Malaysian Ringgit, the impact on SMEs’ performance is still unimpressive, a situation prompting this study to be conducted. A total of 152 companies from the SMEs manufacturing industry in Peninsular Malaysia participated in this study. The data was collected through the survey method. The relationships between the variables were tested using Partial Least Square-Structural Equation Modelling (PLS-SEM) software. Statistical results reveal that a company performance can be significantly affected by innovation and technology adoption risk, along with legal and regulatory environment risk. Furthermore, agility is found to have a moderating effect on the relationship between innovation and technology adoption risk, infrastructure risk, and legal and regulatory environment risk. Overall, the research findings indicate that this analytical model provides a good understanding of the factors influencing the company performance and risk management in Malaysia’s SMEs manufacturing industry.